Batting Performance Analisys of West Java Athletes - Gumilar, Agus; Darajat, Jajat; Ma’mun, Amung; Nuryadi, N; Hambali, Burhan; Mudjihartono, M; Mulyana, Dadan (Universitas Pendidikan Indonesia, 2021)
This research aimed to analyze the batting skill performance on softball using an application of technology. The assessment results can help the coaching process by providing empirical data and become material for evaluation and recommendations for trainers and coaches in the following coaching process. The method used in this research was a descriptive analysis survey. The samples were 21 West Java female softball athletes who were doing training concentration. The measurement of the speed impact parameter was obtained (79.94 ± 7.73) to achieve the 25.06% target achievement. The results of the parameter test on the target obtained a p-value (0.0001) 0.05. This means that the percentage of the results on this parameter had not significantly met the target. The impact time parameter obtained an average percentage of the results of (83.06 ± 8.47). The percentage of the target was 16.94%. The Tukey statistical follow-up test results showed that the impact time parameter had not shown a significant achievement with a p-value (0.0001) 0.05. It concludes that the batting performance of West Java female softball athletes had not reached the stated target. Therefore, it is recommended that the training increase based on the portion and exercise items according to the predetermined parameters.